Costs in beef cattle production: pasture versus feedlot (Research, Society and Development, 2021)
This study aimed to compare the costs of beef cattle production in the fattening modality, in pasture and feedlot systems to identify which of them provides greater profitability to the analyzed cattle rancher. The field of application was a rural property located in the Northern region of the State of Paraná. This is quantitative research, whose data collection instruments consisted of tax documents, accounting information, cost notes in producer's books and bibliographic survey about the treaty. The results showed that the production system that generated lower costs for the rural property under study was pasture, which presented a gain of 37%, while in the containment system the gain was 30%. However, the rural property feedlot system, if optimized, could bring a few advantages such as increased production, lower risk of losses and increased productivity and profitability.